Phototoxic action of light emitting diode in the in vitro viability of Trichophyton rubrum Ação fototóxica do diodo emissor de luz na viabilidade de Trichophyton rubrum in vitro - José Cláudio Faria Amorim; Betania Maria Soares; Orley Araújo Alves; Marcus Vinícius Lucas Ferreira; Gerdal Roberto Sousa; Lívio de Barros Silveira; André Costa Cruz Piancastelli; Marcos Pinotti (Sociedade Brasileira de Dermatologia, 2012)
BACKGROUND: Trichophyton rubrum is the most common agent of superficial mycosis of the skin and nails causing long lasting infections and high recurrence rates. Current treatment drawbacks involve topical medications not being able to reach the nail bed at therapeutic concentrations, systemic antifungal drugs failing to eradicate the fungus before the nails are renewed, severe side effects and selection of resistant fungal isolates. Photodynamic therapy (PDT) has been a promising alternative to conventional treatments. OBJECTIVES: This study evaluated the in vitro effectiveness of toluidine blue O (TBO) irradiated by Light emitting diode (LED) in the reduction of T. rubrum viability. METHODS: The fungal inoculums' was prepared and exposed to different TBO concentrations and energy densities of Light emitting diode for evaluate the T. rubrum sensibility to PDT and production effect fungicidal after photodynamic treatment. In addition, the profiles of the area and volume of the irradiated fungal suspensions were also investigated. RESULTS: A small reduction, in vitro, of fungal cells was observed after exposition to 100 µM toluidine blue O irradiated by 18 J/cm² Light emitting diode. Fungicidal effect occurred after 25 µM toluidine blue O irradiation by Light emitting diode with energy density of 72 J/cm². The analysis showed that the area and volume irradiated by the Light emitting diode were 52.2 mm² and 413.70 mm³, respectively. CONCLUSION: The results allowed to conclude that Photodynamic therapy using Light emitting diode under these experimental conditions is a possible alternative approach to inhibit in vitro T. rubrum and may be a promising new treatment for dermatophytosis caused by this fungus. FUNDAMENTOS: Trichophyton rubrum é o agente mais comum das micoses superficiais de pele e unhas causando infecções de longa duração e altas taxas de recidiva. As desvantagens do tratamento atual envolvem medicações tópicas as quais não são capazes de alcançar o leito ungueal em concentrações terapêuticas, antifúngicos sistêmicos que não erradicam o fungo antes das unhas serem renovadas, efeitos colaterais graves e seleção de isolados fúngicos resistentes. A terapia fotodinâmica tem sido uma alternativa promissora aos tratamentos convencionais. OBJETIVOS: Este estudo avaliou a eficácia, in vitro, de azul de orto-toluidina irradiado por diodo emissor de luz na redução da viabilidade de T. rubrum. MÉTODOS: O inóculo fúngico foi preparado e exposto a diferentes concentrações de azul de orto-toluidina e densidades de energia do diodo emissor de luz, para avaliar a sensibilidade de T. rubrum e o efeito fungicida, após terapia fotodinâmica. Além disso, os perfis da área e volume das suspensões fúngicas irradiados também foram investigados. RESULTADOS: Uma pequena redução, in vitro, de células fúngicas foi observada após a exposição a 100 mM azul de orto-toluidina irradiados por diodo emissor de luz a 18 J/cm². Efeito fungicida ocorreu após irradiação 25 µM orto-toluidina por diodo emissor de luz com densidade de energia de 72 J/cm². A análise mostrou que a área e o volume irradiados pelo diodo emissor de luz foram 52,2 mm² e 413,70 mm³, respectivamente. CONCLUSÕES: Os resultados permitiram concluir que a terapia fotodinâmica com diodo emissor de luz, nas condições experimentais é uma abordagem alternativa para inibir, in vitro, T. rubrum e pode ser um tratamento promissor para as dermatofitoses causadas por este fungo.